PENGARUH GREEN ACCOUNTING DAN CARBON EMISSION DISCLOSURE TERHADAP NILAI PERUSAHAAN MELALUI MAQASHID SYARIAH - Al Banjari, Naufal Rizqullah (Jurnal Riset Akuntansi Politala, 2023)
This study aims to analyze direct influence between green accounting, carbon emission disclosure, and maqashid sharia variables on firm value and analyze indirect influence between green accounting and carbon emission disclosure on firm value through maqashid sharia as intervening variable in state-owned companies listed in Indonesian Sharia Stock Index in the 2017-2021 period. This study is a quantitative research with an associative approach. The type of data used is secondary data by using documentation techniques in retrieving data in the form of annual reports and sustainability reports in each company. The data analysis technique used is structural equation modeling (SEM) analysis with the partial least square (PLS) method, then all of which will be processed in the SmartPLS 3 application. The result of this study are there is no significant effect between green accounting and carbon emission disclosure on firm value and maqashid sharia, while maqashid sharia has a significant influence on firm value. Meanwhile, there is no indirect effect between green accounting and carbon emission disclosure on firm value through maqashid sharia.